O Sistema de Notificação VIVA como importante fonte de dados da Violência Infantil no Brasil: uma análise das notificações compulsórias do ano 2011 - Suzana Maria Moreira Rattes (2016)
Objective: To describe and analyse violence reports against children from 0 to 9 years of age issued by the public health services in Brazil. Methods: The data used were extracted from the Surveillance of Violence and Injuries of Notifiable Diseases Information System (Viva-SINAN). The frequency of selected variables was calculated by age group (0-1; 2-5 and 6-9 years of age) as well as their Prevalence Ratios (PR). Results: 17.900 cases were reported, 33% in group 0-1 years, 35,8% in 2-5 years and 31,2% in 6-9 years. The physical violence predominated in boys, 6-9 years old. Sexual violence predominated in girls, brown/black, 6-9 years and with more chance to occur at home; psychological violence prevailed in girls, brown/black, 6-9 years old, at home; negligence occurred more in boys; 0-1 years and their parents as the main aggressors. Conclusion: The results indicate the importance of VIVA System as a source of information for the development of studies that support the network strengthening social protection and care.